The history of US-Japan relations from Perry to the present - Iokibe, Makoto 1943-; Minohara, Toshihiro 1971- (2017)
Examining the 160 year relationship between America and Japan, this cutting edge collection considers the evolution of the relationship of these two nations which straddle the Pacific, from the first encounters in the 19th century to major international shifts in a post 9/11 world. It examines the emergence of Japan in the wake of the 1905 Russo-Japanese War and the development of U.S. policies toward East Asia at the turn of the century. It goes on to study the impact of World War One in Asia, the Washington Treaty System, the issue of Immigration Issue and the deterioration of US-Japan relations in the 1930s as Japan invaded Manchuria. It also reflects on the Pacific War and the Occupation of Japan, and the country's postwar Resurgence, democratization and economic recovery, as well as the maturing and the challenges facing the US Japan relationship as it progresses into the 21st century. This is a key read for those interested in the history of this important relationship as well as for scholars of diplomatic history and international relations.
America encounters Japan, 1836-94 Tosh Minohara and Kaoru Iokibe -- The emergence of Japan on the global stage, 1895-1908 Yasutoshi Teramoto and Tosh Minohara -- The Great War and shifting relations, 1909-1919 Tosh Minohara, Sh?usuke Takahara, and Ry?ota Murai -- The 1920s : the Washington treaty system and the immigration issue Ry?uji Hattori and Tosh Minohara -- The 1930s : Japan's war with China and American non-recognition Fumiaki Kubo, Ry?uji Hattori, and Satoshi Hattori -- The Pacific War and the occupation of Japan, 1941-52 Futoshi Shibayama and Ayako Kusunoki -- The 1950s : Pax Americana and Japan's postwar resurgence Takuya Sasaki and Hiroshi Nakanishi -- The 1960s : Japan's economic rise and the maturing of the partnership Makoto Iokibe and Takuya Sasaki -- The 1970s : stresses on the relationship Yoshihide Soeya and Robert D. Eldridge -- The 1980s : the decade of neoliberalism Akihiko Tanaka and Masayuki Tadokoro -- The 1990s : from a drifting relationship to a redefinition of the alliance K?oji Murata -- US-Japan leadership in the post-9/11 world Makoto Iokibe and Fumiaki Kubo -- Afterword of the English translation edition -- Chronology of events.
Includes bibliographical references (pages 325-335) and index.
Japan Foundation
Translated from the Japanese.
Keywords: United States -- Foreign relations -- Japan; Japan -- Foreign relations -- United States; United States -- Foreign relations -- 1865-.; Japan -- Foreign relations -- 1868-.